STUDIES ON CERVICAL MUCOUS OF PATIENTS TAKING LYNESTRENOL AS CONTRACEPTION - H.NAFICY; H.PARSA (Tehran University of Medical Sciences, 1973)
Lynestrenol 0.5 mg.(Exlution) given to patients orally from the first day of their cycle in a continuous manner suppressed cervical mucorrhea and spinbarkeit sufficiently ennough to stop sperm penetration to the cervical canal. Fern reactions were mostly negative and all post- coital examinations (Sims Huhner tests) showed an absence of spermatozoa.